2019
DOI: 10.3847/2041-8213/ab40c5
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Emission Post Spinning Black Hole Magnetized Neutron Star Mergers

Abstract: For a binary composed of a spinning black hole (BH) (with mass 7M ⊙ ) and a strongly magnetized neutron star (NS) (with surface magnetic field strength B S,NS 10 12 G and mass ∼ 1.4M ⊙ ), the NS as a whole will possibly eventually plunge into the BH. During the inspiral phase, the spinning BH could be charged to the Wald charge quantity Q W until merger in an electro-vacuum approximation. During the merger, if the spinning charged BH creates its own magnetosphere due to an electric field strong enough for pair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…They consider EM signatures at radio frequencies, but other manifestations of this energy transport are possible and require further study. A number of recent works have also begun to develop possible signatures due to charging and discharging of the BH via the Wald (1974) mechanism (Chen & Dai 2021;Levin et al 2018;Dai 2019;Zhang 2019;Pan & Yang 2019;Zhong et al 2019;Yang et al 2020b). Interestingly many of these mechanisms still have total power that scales with the square of the magnetic field strength, but expected energies of emission will likely vary.…”
Section: Non-fireball Emissionmentioning
confidence: 99%
“…They consider EM signatures at radio frequencies, but other manifestations of this energy transport are possible and require further study. A number of recent works have also begun to develop possible signatures due to charging and discharging of the BH via the Wald (1974) mechanism (Chen & Dai 2021;Levin et al 2018;Dai 2019;Zhang 2019;Pan & Yang 2019;Zhong et al 2019;Yang et al 2020b). Interestingly many of these mechanisms still have total power that scales with the square of the magnetic field strength, but expected energies of emission will likely vary.…”
Section: Non-fireball Emissionmentioning
confidence: 99%
“…Specifically, the tidal disruption is required to occur outside the innermost stable circular orbit of the black hole for inducing astrophysically interesting outcomes. If the neutron star is not disrupted, as is likely the case of GW200105 and GW200115, it behaves like a point particle throughout the coalescence, and the merger process will be indistinguishable from that of (highly asymmetric) binary black holes (Foucart et al 2013a) except for possible electromagnetic emission associated with crust shattering (Tsang et al 2012), magnetospheric activities (Hansen and Lyutikov 2001;McWilliams and Levin 2011;Lai 2012;Paschalidis et al 2013;D'Orazio et al 2016;Carrasco and Shibata 2020;Wada et al 2020;East et al 2021;Carrasco et al 2021, see also Ioka and Taniguchi 2000 for earlier work on binary neutron stars), or charged black holes (Levin et al 2018;Zhang 2019;Dai 2019;Pan and Yang 2019;Zhong et al 2019). These two possibilities for the fate of merger are summarized schematically in Fig.…”
mentioning
confidence: 99%
“…For an NS-BH merger with a relatively large q (e.g., ∼ 5), the NS would plunge into the BH as a whole so alternative mechanisms (e.g., McWilliams & Levin 2011;Tsang et al 2012;D'Orazio et al 2016;Levin et al 2018;Zhang 2019a;Dai 2019;Pan & Yang 2019;Zhong et al 2019) have to be introduced to explain the observed GRB. One group of the mechanisms which recently receives increasing interest are the electric and magnetic dipole radiation, magnetic reconnection, and BZ mechanism of the charged objects in the binary system.…”
Section: Plunging Ns-bh Merger or Bh-bh Merger: Constraints On Charge...mentioning
confidence: 99%
“…The charged compact binary coalescence (cCBC) models involve at least one member of the binary carries either a constant (Zhang 2016(Zhang , 2019a or increasing (Levin et al 2018;Dai 2019) charge. The high-energy EM emission can be produced either before (Zhang 2019a;Dai 2019) or after (Pan & Yang 2019;Zhong et al 2019) the merger.…”
Section: Plunging Ns-bh Merger or Bh-bh Merger: Constraints On Charge...mentioning
confidence: 99%
See 1 more Smart Citation